MARKETING COMMUNICATION STRATEGY IMPLEMENTED BY COLOR PRODUCTION IN PROMOTING AND SELLING THEIR SERVICES - Nurfitrah; Seny Luhriyani Sunusi; Andi Hajar; Himala Praptami Adys; Ahmad Azhari (International Journal of Business English and Communication, 2025)
The objective of this research is to examine the implementation of the marketing communication strategy (the 7Ps of the marketing mix) as well as to identify the inhibiting factors in the promotion and sale of services. This study employed a qualitative research design with a descriptive approach to provide a comprehensive understanding of the research subject. Data were collected through observation and interviews. The findings reveal that Color Production utilizes the 7Ps marketing mix product, price, place, promotion, people, physical evidence, and process in its business practices. Additionally, the study identified several inhibiting factors affecting the promotion and sale of services, including limited capital, competition, and pricing challenges. The results suggest that an effective marketing communication strategy plays a crucial role in increasing sales and attracting customers.